41 Age Modifies the Association between Apathy ANND Recurrent Falling in Dutch Ambulant Older Persons with a High Fall Risk. (20th December 2019) - Henstra, Marieke; Houbolt, Carin; Seppala, Lotta; De Rooij, Sophia; Rhebergen, Didi; Stek, Max; Van der Velde, Nathalie
Abstract: Apathy, a common and disabling behavioural syndrome in older persons, has been associated with impaired physical performance and executive dysfunction. Both are fall risk factors and they share pathophysiological pathway. We cross-sectionally examined the association between apathy and recurrent falling (≥2 falls in the past 12 months) and number of falls in the past 12 months in 243 outpatients aged ≥ 65 years with ≥3 fall risk-factors visiting a fall-clinic after a fall. We calculated Odds Ratio's (ORs), Incidence Rate Ratio's (IRRs) and their 95% Confidential Intervals (CI95) using multivariable regression and negative binomial regression analyses. We adjusted for cognitive functioning, depression, the use of fall risk increasing drugs, visual impairment, urine incontinence, comorbidity, smoking, use of alcohol, body mass index (BMI), and the number of months between assessment of fall risk and of apathy. We assessed effect modification by age and gender. In our study, apathy was independently associated with recurrent falling in patients aged 65-75 years: OR 2.8 (CI95 1.0-7.7). Overall, patients with apathy experienced 1.46 times as many falls in the past 12 months compared to patients without apathy (IRR 1.46 (CI95 1.0-2.1). To conclude, in high fall-risk older outpatients, apathy was cross-sectionally associated with recurrent falling in patients aged 65-75 years and the number of falls. Apathy appeared to be especially relevant in relation to falling in this age group. Whether apathy predicts recurrent falling is yet to be determined.